Designing Fiscal Policy to Address the External Costs of Energy - Ian Parry (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper first reviews the conceptual case for, and appropriate design of, fiscal policies to address major externalities associated with energy useglobal warming, local air pollution, and various side effects (e.g., congestion) from motor vehicles. Techniques for (roughly) estimating the magnitude of these externalities, and corrective energy taxes, on a country-by-country basis are then described. The implications for reforming energy taxes, and the potential environmental, health, and fiscal benefits from reform, are then discussed. A theme of the paper is the critical role of finance ministries in administering tax reforms and ensuring efficient use of revenues.
Keywords: H23; Q48; Q54; Q58; 330; externalities; energy taxes; getting prices right; air pollution; global warming